Maternal mortality and morbidity amongst antenatal patients with and without COVID-19 infection - Kharakwal, Sushila; Sharma, Anshul; Mishra, Prerana (International Journal of Advances in Medicine, 2023)
Background: The aim of our study is to compare the maternal mortality between those who are infected with COVID-19 infection and those who are not. Our study was done at Maharani Laxmi Bai Medical College, Jhansi, Uttar Pradesh, which included 2 groups: group 1- pregnant women with COVID-19 infection, and group 2- pregnant women without COVID-19 infection. Methods: Our study is prospective and comparative study, done over 250 antenatal patients admitted at our centre, with COVID-19 infection status confirmed either by rapid antigen testing, or by reverse transcription polymerase chain reaction (RT-PCR)/TruNaat testing who had signs and symptoms of COVID-19 infection along with those who needed obstetric intervention or had a high-risk pregnancy status. Results: Preterm labor accounted for the maternal complication with a majority in COVID-19 infected maternal group. Maternal mortality did not increase amongst patients affected with COVID-19 infection within our study duration. Conclusions: Maternal mortality thus did not seem to be affected much by the COVID-19 pandemic probably due to the low infectivity and fatality of third wave was low.